2023
DOI: 10.1111/nph.19180
|View full text |Cite
|
Sign up to set email alerts
|

NCR343 is required to maintain the viability of differentiated bacteroids in nodule cells in Medicago truncatula

Abstract: Summary Bacteroid (name for rhizobia inside nodule cells) differentiation is a prerequisite for successful nitrogen‐fixing symbiosis. In certain legumes, under the regulation of host proteins, for example, a large group of NCR (nodule cysteine rich) peptides, bacteroids undergo irreversible terminal differentiation. This process causes them to lose the ability to propagate inside nodule cells while boosting their competency for nitrogen fixation. How host cells maintain the viability of differentiated bacteroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Selecting of NCR genes to be targeted by CRISPR/Cas9 editing The M. truncatula genome contains a large gene family coding for more than 700 NCR peptides but only few of them, NCR169, NCR211, NCR247, NCR343 and NCR-new35, have been proved to be crucial for symbiosis [10][11][12][13][14][15] . The sequences of the essential NCR genes are highly variable, and their common feature is that they contain four cysteine residues in conserved positions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Selecting of NCR genes to be targeted by CRISPR/Cas9 editing The M. truncatula genome contains a large gene family coding for more than 700 NCR peptides but only few of them, NCR169, NCR211, NCR247, NCR343 and NCR-new35, have been proved to be crucial for symbiosis [10][11][12][13][14][15] . The sequences of the essential NCR genes are highly variable, and their common feature is that they contain four cysteine residues in conserved positions.…”
Section: Resultsmentioning
confidence: 99%
“…NCRs compose a large gene family with more than 700 members 9 in M. truncatula and because this large number of NCRs, their function was thought to be redundant. The identi cation of few individual NCRs crucial for nitrogen-xing symbiosis disproved this concept [10][11][12][13][14][15] . These essential NCRs except for NCR247, which was analysed by reverse genetic approach, were identi ed fortuitously using deletion mutant collections of M. truncatula.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this high number of peptides show remarkable amino acid sequence variation, their function was initially presumed redundant. Nevertheless, recent studies have identified some peptides, NCR169, NCR211, NCR247, NCR343 and NCR-new35, crucial for the bacteroid differentiation and persistence in M. truncatula nodules but also found peptides (NCR178, NCR341, NCR344 and NCR345) which are not essential for nitrogen-fixing symbiosis [10][11][12][13][14][15] . The identification of most of these essential peptides was random during the forward genetic analyses of mutagenized M. truncatula populations.…”
mentioning
confidence: 99%